Nexus of inquiry-based instruction, active learning and formative assessment in education / Chan Yuen Fook - Chan, Yuen Fook (Akademi Pengajian Bahasa, 2021)
In today’s flexible learning and virtual space environments, the way forward for leading change has witnessed a shift towards inquiry-based instruction, active learning and formative assessment. This has also been well articulated by the many initiatives from the Malaysian Ministry of Education through the launch of two national education blueprints. As the nation journeys into 21st century, practitioners in Malaysia are taking incremental steps in shifting from teacher-centred to student-centred learning environments in a bid to prepare millennials for the keen competitive markets of tomorrow. Such a move, warrants a critical and timely move towards the adoption of a more comprehensive and effective structure of curriculum which focuses on inquiry-based instruction and active learning approaches that are able to provide on-going constructive feedback via formative assessment that can positively affect learners and their learning experience. This paper discusses two main issues. First, it deliberates inquiry-based instruction, active learning and formative assessment. Then it discusses the nexus of relationship among the variables with evidence of empirical studies and concludes with some recommendations for both universities and educational practitioners alike to enhance teaching and learning experience in their respective classrooms.